ANALISIS KETERAMPILAN BERPIKIR KRITIS MAHASISWA CALON GURU BIOLOGI MELALUI PEMBELAJARAN KOOPERATIF PADA MATA KULIAH DESAIN PEMBELAJARAN 2014/2015 - Pratiwi, Dasrieny (Universitas Tanjungpura, 2015)
This research was held in order to contribute in mapping of the students’ critical thinking while they were taking Instructional Design (DesainPembelajaran) as their subjects. The implementation of this subject used Cooperative Learning Model to form their critical thinking. The scores in this research were obtained through some tests which were taken at the end of the lecture. Meanwhile, the study implementation was collected using the observation sheets. As results, the students’ critical thinking was mapped into three groups; they are upper, middle, and lower groups. The numbers respectively were 22.45%; 51.02%; and 26.53%. Furthermore, the upper group’s students also gained the highest scores in the observed implementation. It is revealed that the discussion during the Learning Cooperative study was able to form the students’ critical thinking. Keyword: Critical thinking skill, cooperative learning.